Estimation of Urea Reduction Ratio in Dialysis Patients Per Session and Adequacy of Dialysis - Aniqa Atta, Muhammad Nasir Khan, Pervez Muhammad, Muhammad Zubair, Ahmad Shamim Khan, Yousaf Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Chronic kidney disease is a condition in which the kidney is no more able to remove waste from the body. Through hemodialysis, the excess water and waste from the blood are removed such as urea and creatinine. The urea reduction ratio is a measure of the proportionate reduction in urea blood nitrogen throughout dialysis. It is an acceptable, easy and simple method globally to find dialysis adequacy that how much urea is removed from the body. Our study was aimed at assessing the targets to achieve the urea reduction ratio (URR), in chronic kidney disease patients who underwent hemodialysis. Methods: The pre-dialysis and post-dialysis blood samples were collected from 80 hemodialysis patients. A Performa was filled, blood pressure was monitored before mid and at the end of the session, weight was monitored and ultrafiltration for the adequacy of the dialysis. The urea reduction ratio (URR) was calculated by (pre dialysis urea – post-dialysis urea) divided by pre-dialysis urea and it is expressed in percentage. Results: The mean urea reduction rate (URR) was 74% (adequate URR is >65%). The results of the pre-dialysis and post-dialysis serum urea levels. There was a significant reduction in these parameters, thus suggesting the adequacy of the dialysis. There was the achievement of the target goal. But the inadequacy was also seen at 54.7%. Conclusion: The targeted urea reduction ratio was achieved in the setup of Khyber teaching hospital, but for inadequacy, they need a lot of follow-up and supervision.